2009
DOI: 10.1161/strokeaha.108.525709
|View full text |Cite
|
Sign up to set email alerts
|

Embolic Potential of Cardiac Tumors and Outcome After Resection

Abstract: Background and Purpose-Embolic events have long been thought to occur in patients with cardiac tumors secondary to embolization of tumor fragments; however, there are no large studies examining the epidemiology and occurrence of embolism in this group of patients. Methods-From

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
70
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 33 publications
0
70
1
8
Order By: Relevance
“…A recent study suggested that surgical resection in the context of a recent embolic event, including ischemic stroke, is safe, with excellent long-term outcomes in patients with cardiac tumors. 9 In our case, surgical tumor resection was safe and successful, resulting in no neurologic deterioration and prolongation of life.…”
Section: Discussionmentioning
confidence: 50%
“…A recent study suggested that surgical resection in the context of a recent embolic event, including ischemic stroke, is safe, with excellent long-term outcomes in patients with cardiac tumors. 9 In our case, surgical tumor resection was safe and successful, resulting in no neurologic deterioration and prolongation of life.…”
Section: Discussionmentioning
confidence: 50%
“…Interference with the heart valves or direct invasion of the myocardium can also cause arrhythmia, heart block, or pericardial effusion [6, 8]. …”
Section: Discussionmentioning
confidence: 99%
“…Emboli may arise from tumor fragmentation or detachment of the entire tumor or from thrombi or infected foci on the neoplasm [4,23]. Three patients in this cohort (2 with papillary fibroelastoma and 1 with sarcoma) presented with cerebral embolism, which is associated with these pathological types [11,31]. The incidence of embolism varies with different tumors and is believed to be related to the size and mobility of the tumor [27,32].…”
Section: Discussionmentioning
confidence: 99%